2001
DOI: 10.1006/viro.2001.1083
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection of B Lymphocytes by Bovine Respiratory Syncytial Virus

Abstract: Bovine respiratory syncytial virus (BRSV) is a major cause of respiratory disease in young cattle. Here we demonstrate BRSV persistence at low levels in tracheobronchial and mediastinal lymph nodes up to 71 days after the experimental infection of calves. Positive results were obtained on viral genomic RNA and messenger RNA coding for the nucleoprotein, glycoprotein (G), and fusion protein (F). G and F proteins were also detected in the pulmonary lymph nodes by immunohistochemistry. Double-staining experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 65 publications
0
46
0
5
Order By: Relevance
“…Several animal studies suggest that latent infection with RSV is possible. RSV proteins and genomic RNA have been detected in the lungs of experimentally infected guinea pigs 2 mo after infection and persistent infection of B lymphocytes by bovine RSV has also been demonstrated (27,28). More recently, Schwarze and colleagues have recovered low levels of infectious virus from the lungs of T-cell-depleted mice 150 d after the initial intranasal infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies suggest that latent infection with RSV is possible. RSV proteins and genomic RNA have been detected in the lungs of experimentally infected guinea pigs 2 mo after infection and persistent infection of B lymphocytes by bovine RSV has also been demonstrated (27,28). More recently, Schwarze and colleagues have recovered low levels of infectious virus from the lungs of T-cell-depleted mice 150 d after the initial intranasal infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the mononuclear cell staining in this current study was morphologically consistent with macrophages, and given the intracytoplasmic viral inclusions, direct RSV infection of macrophages was most likely. Other mononuclear cells such as dendritic cells and lymphocytes cannot be excluded, as in vitro studies have shown capacity for RSV uptake [44,45]. As for neutrophil antigen accumulation, phagocytosis of sloughed infected cellular debris in airways probably allowed for much of the neutrophil staining, since there was a lack of distinct cytoplasmic inclusions, and the quick demise of the degenerate neutrophil following exocytosis into the airway lumen would prevent opportunity for adequate viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…BRSV is mainly transmitted by direct contact between infected animals or by aerosol [94] but it cannot be excluded that it might also be spread by humans acting as a passive vector as observed for HRSV [55]. Some data indicate that BRSV may persist in infected animals [39,140,151]. However attempts to demonstrate re-excretion of BRSV from previously infected animals by treatment with 3-methyl indol, BVDV, BHV1 or dexamethasone have failed [158] and transmission of virus from carriers to susceptible animals has not been proven.…”
Section: Epidemiologymentioning
confidence: 99%